Pre-planting microbial treatments for onion growth enhancement - Kholdorov Mirkhalil; Aripova Shakhnoza; Ortikova Ezoza; Karimova Charos; Berdiyorov Khurshidjon; Normatova Maftuna (BIO Web of Conferences)
In agriculture, the fight against pests, diseases and weeds is of great importance in the production of food products, obtaining a high-quality, high yield. Carrying out such activities allows to save 30% additional harvest. It has been determined that 40% of agricultural crops are lost annually due to harmful organisms. Only 13.8% of agricultural products and 8.4% of vegetable crops die due to pests. According to scientists’ calculations, 3 million tons of vegetable products can be saved every year in the CIS countries alone by timely effective control of harmful organisms. This article provides information on the microbiological analysis of onion seeds when treated with microbiological preparations and the effect of seeds on plant growth, bulb formation, leaf number, leaf length and yield when planted in the ground. The obtained results showed that when onion seeds were planted with microbiological preparations, an additional 1.0-0.7-0.3 t/ha was obtained due to the accelerated development of plants planted without treatment.